Reseaching the PVT properties and gradient energy coefficient with different parameters of Polystyrene (PS910) - S. M. Nuri; S.Y.Darweesh (Tikrit Journal of Pure Science)
The Gradient energy coefficient ( ) in polymers and oligomers are playing an important role in polymer as well as understanding of many processes especially in innovation of new polymer with classification of materials.. As a result, the main reason  in this study appear which has how the gradient energy coefficient changes from bulk to surface., has been establishing the new chemical potential equation as well helped us  to extract the correlation between gradient energy coefficient and different parameters. The gradient energy coefficient has been related with hole fractions, temperature  and density. Both Simha-Somcynsky (SS) and Cahn-Hilliard (CH) models are  employed  together to calculate the thermodynamic properties of polystyren.,These studies are written in a code program (Mathematica). At first pressure-volume-temperature (PVT) data for the SS theory, are calculated from the modified cell model (MCL) starting atmospheric pressure to 150 Mpa and temperature range from 313 to 473 K, as well. The PVT characteristic parameters of the SS theory are calculated using the data, with the average and maximum value of percentage deviation of specific volume are reported below 0.117 and 0.415 respectively.